2009
DOI: 10.1128/aem.02357-08
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Independent Characterization of Bacterial Communities Associated with the Cold-Water Coral Lophelia pertusa in the Northeastern Gulf of Mexico

Abstract: Bacteria are recognized as an important part of the total biology of shallow-water corals. Studies of shallow-water corals suggest that associated bacteria may benefit the corals by cycling carbon, fixing nitrogen, chelating iron, and producing antibiotics that protect the coral from other microbes. Cold-water or deep-sea corals have a fundamentally different ecology due to their adaptation to cold, dark, high-pressure environments and as such have novel microbiota. The goal of this study was to characterize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
4
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 65 publications
8
116
4
1
Order By: Relevance
“…This can be explained by mucus-specific microbial communities as described for warm-water corals (Ritchie & Smith 2004, Ritchie 2006, Kooperman et al 2007, Allers et al 2008. Such an explanation is also supported for cold-water corals by the studies of Neulinger et al (2008) and Kellogg et al (2009), which indicate that L. pertusa-specific microbial communities exist. Furthermore, the study of Schöttner et al (2009), showed that different L. pertusa-and Madrepora oculata-generated habitats, including the coral-derived mucus surface layer, offer niches for specific microbial communities.…”
Section: Degradability Of Lophelia Pertusa-derived Mucus and Associatmentioning
confidence: 68%
“…This can be explained by mucus-specific microbial communities as described for warm-water corals (Ritchie & Smith 2004, Ritchie 2006, Kooperman et al 2007, Allers et al 2008. Such an explanation is also supported for cold-water corals by the studies of Neulinger et al (2008) and Kellogg et al (2009), which indicate that L. pertusa-specific microbial communities exist. Furthermore, the study of Schöttner et al (2009), showed that different L. pertusa-and Madrepora oculata-generated habitats, including the coral-derived mucus surface layer, offer niches for specific microbial communities.…”
Section: Degradability Of Lophelia Pertusa-derived Mucus and Associatmentioning
confidence: 68%
“…Mollicutes are widespread commensals or pathogens of humans, mammals, reptiles, fish, plants, and other arthropods (reviewed in reference 67) and have also been reported to be associated with different invertebrates, e.g., earthworms (12), isopods (11), oysters (68,69), crustaceans (10), bryozoans (70), ctenophores (63,71), and also cnidarians (72)(73)(74). Parasitic, commensal, and mutualistic endosymbioses are widely distributed among invertebrate taxa and have arguably played a major role in the evolution of several invertebrate families, classes, and phyla (75).…”
Section: Discussionmentioning
confidence: 99%
“…However, mainly due to their limited accessibility, the knowledge on deep-sea corals is still scarce, especially in regard to their associated microbial communities. Few studies characterized deep-sea coral associated bacterial communities, focusing mainly on octocorals (Penn et al, 2006;Gray et al, 2011;Kellogg et al, 2016;Lawler et al, 2016) and two reef-building scleractinian corals, namely Lophelia pertusa and Madrepora oculata (Yakimov et al, 2006;Neulinger et al, 2008Neulinger et al, , 2009Hansson et al, 2009;Kellogg et al, 2009Kellogg et al, , 2017Schöttner et al, 2009Schöttner et al, , 2012Galkiewicz et al, 2011;Emblem et al, 2012;van Bleijswijk et al, 2015;Meistertzheim et al, 2016). Findings include species-specific microbiomes, but also considerable spatial and temporal variations.…”
Section: Introductionmentioning
confidence: 99%